Epigenetic modifier Kdm6a/Utx controls the specification of hypothalamic neuronal subtypes in a sex-dependent manner - Cabrera Zapata, Lucas E.; Cambiasso, María Julia; Arevalo, Maria Angeles (Frontiers in Cell and Developmental Biology, 2022)
Kdm6a is an X-chromosome-linked H3K27me2/3 demethylase that promotes chromatin accessibility and gene transcription and is critical for tissue/cell-specific differentiation. Previous results showed higher Kdm6a levels in XX than in XY hypothalamic neurons and a female-specific requirement for Kdm6a in mediating increased axogenesis before brain masculinization. Here, we explored the sex-specific role of Kdm6a in the specification of neuronal subtypes in the developing hypothalamus. Hypothalamic neuronal cultures were established from sex-segregated E14 mouse embryos and transfected with siRNAs to knockdown Kdm6a expression (Kdm6a-KD). We evaluated the effect of Kdm6a-KD on Ngn3 expression, a bHLH transcription factor regulating neuronal sub-specification in hypothalamus. Kdm6a-KD decreased Ngn3 expression in females but not in males, abolishing basal sex differences. Then, we analyzed Kdm6a-KD effect on Ascl1, Pomc, Npy, Sf1, Gad1, and Th expression by RT-qPCR. While Kdm6a-KD downregulated Ascl1 in both sexes equally, we found sex-specific effects for Pomc, Npy, and Th. Pomc and Th expressed higher in female than in male neurons, and Kdm6a-KD reduced their levels only in females, while Npy expressed higher in male than in female neurons, and Kdm6a-KD upregulated its expression only in females. Identical results were found by immunofluorescence for Pomc and Npy neuropeptides. Finally, using ChIP-qPCR, we found higher H3K27me3 levels at Ngn3, Pomc, and Npy promoters in male neurons, in line with Kdm6a higher expression and demethylase activity in females. At all three promoters, Kdm6a-KD induced an enrichment of H3K27me3 only in females. These results indicate that Kdm6a plays a sex-specific role in controlling the expression of transcription factors and neuropeptides critical for the differentiation of hypothalamic neuronal populations regulating food intake and energy homeostasis.